OLD — YOUNG — OLD MAN: DYNAMICS OF SUBJECTIVE WORD SEMANTICS (Филологический класс, 2018)
Ways to diagnose the development of subjective semantics of the word is one of the urgent problems of modern psycholinguistics. The article shows the dynamics of the polysemantic word “old” as a system of semantic components and their connections existing in the minds of native speakers of the Russian language. The psycholinguistic approach to the analysis of the associative semantics of a polysemantic word, addressed both to the human world and to the world of inanimate objects was applied. The object of the research is the importance of the lexeme as a property of Russian speakers and a fragment of their linguistic consciousness. The subject is the semantic composition, the nature of changes in the semantics of the adjective as the basis for the psycholinguistic modeling of the views of the Russian speakers on the corresponding quality in different periods of the society's life. The research is based on the hypothesis that the meaning of the word of any part of speech changes in the course of time. The author analyzes the structure of the associative field of the lexeme “old” in the main associative bases of the Russian language, reveals the change in the core of the lexeme and its periphery in different times, and draws conclusions about the qualitative and quantitative rearrangement of the field. It was found that the nucleous changes due to the change of ranks of the main components; the near periphery due to transition of components from the nucleus and far periphery, and the far periphery due to enlargement of the number of components. The study found that a significant part in every area in all fields is occupied by the layer of subjects, and it contains the cognitive space of subjects by age, sex, proximity, kinship ties. An increase in the stereotyping of relationships took place in the last decade. The layer of subjects of the objective world increased in number in the period from the 1970s to the 1990s, which indicates the tendency of the semantics of the stimulus to be presented in this segment. On the other hand, the layer of characteristic decreased somewhat from the 1960s to the 1990s, preserving stability in the 21st century, pointing to the importance of this semantics parameter for native speakers.